The Role Of Succession Planning In Human Capital Development In Organizations ( the Field of the research at the Oil Training Institute – Baghdad - Hasan Al-Muttairi, Mohammed Khalaf; Abid Al-Zeidi, Nadhum Jawad (Journal of Economics and Administrative Sciences, 2021)
To identify the importance of the role of succession planning in developing human capital in organizations in light of the accelerating and dynamic events and changes in the work environment, and the research problem indicated the seriousness of employees retiring or leaving their positions for any reason and the extent of its impact on the organization in creating gaps in leadership and problems In managing the talent injection because there will be a shortage of talent, which in turn will affect the general performance of the business in the researched institute, so the importance of research appears in trying to present a set of solutions through which some of the problems facing the organization in question are addressed to the extent that it relates to the variables studied. .The researcher relied on the questionnaire as a main tool for the purpose of collecting research data, and it was prepared based on two ready-made scales after they were subjected to validity and stability tests to suit the research objectives, in addition to the researcher's adoption of the method of personal interviews relying on some questionnaire questions for the purpose of verifying credibility In the answer, it was distributed to a sample of (66) employees at the Baghdad Oil Training Institute, and the ready-made statistical program (SPSS. V. 22) was used to enter the data obtained and analyze it .The statistical tools used in the analysis produced a set of results, all of which confirmed the existence of a statistically significant correlation and influence between the investigated variables in a manner that confirms the validity of the research hypotheses, so the researcher concluded the importance of the role of succession planning in developing human capital and enhancing knowledge, capabilities and capabilities of employees and thus their industry as substitutes Ready for career succession . The current research provides a basis for adopting the concept of succession planning and its effective role in developing human resources in organizations and providing potential successors to fill the need, whether naturally or emergency, to avoid the organization's state of confusion and dispersion